EVALUATION OF THE POTENTIAL USE OF PHYSIC NUT (JATROPHA CURCAS L.) FOR THE GENERATION OF BIOFUEL - Villafuerte-Barreto, Ariel Gonzalo (2023)
The present work has as its main objective to evaluate the potential of the use of physic nut (Jatropha curcas L). for the generation of biofuel, through a literature review. The physic nut is a shrub of economic importance, due to its various industrial uses. It is relevant for the development of bioenergy, due to the high concentration of oil in its seeds, which is why it is used for the production of biodiesel, while the shells of its fruits can be considered for the production of ethanol due to its high cellulose content. The cake obtained after the oil extraction process is a useful organic by-product that contains considerable amounts of macro and micronutrients, being suitable for agricultural use as organic fertilizer, and if the cake goes through a detoxification process, it can be used as animal feed.